1989
DOI: 10.1002/eji.1830190214
|View full text |Cite
|
Sign up to set email alerts
|

L3T4 T cells promoting susceptibility to murine cutaneous leishmaniasis express the surface marker Ly‐24 (Pgp‐1)

Abstract: In a murine model of cutaneous leishmaniasis, the importance of T cell‐dependent immunity has been documented by the susceptibility to parasite infection of athymic nude mice of both genetically resistant and genetically susceptible strains. T lymphocytes from uninfected mice have the capacity to promote resistance to Leishmania major infection in nude recipients, whereas T cells from mice chronically infected with L. major not only fail to mediate protection, but totally abrogate the host‐protective effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
1993
1993

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…It would be in analogy to the human system, where the functionally distinct T cell subsets CD45R+ and CDw29+ have been shown to represent distinct activation stages but not separate cell lineages [32]. In murine cutaneous leishmaniasis, we have recently shown that a disease-promoting effect can only be mediated by activated CD4+ cells from chronically infected BALB/c mice, expressing the surface marker Ly-24 (CD44), but not by resting CD4+Ly-24-cells [33]. In the present LD studies, it is notable that IL2 production by CD4+ cells from susceptible mice was never paired with significant secretion of IFN-y.…”
Section: Discussionmentioning
confidence: 99%
“…It would be in analogy to the human system, where the functionally distinct T cell subsets CD45R+ and CDw29+ have been shown to represent distinct activation stages but not separate cell lineages [32]. In murine cutaneous leishmaniasis, we have recently shown that a disease-promoting effect can only be mediated by activated CD4+ cells from chronically infected BALB/c mice, expressing the surface marker Ly-24 (CD44), but not by resting CD4+Ly-24-cells [33]. In the present LD studies, it is notable that IL2 production by CD4+ cells from susceptible mice was never paired with significant secretion of IFN-y.…”
Section: Discussionmentioning
confidence: 99%